UPAYA PEMBINAAN KETAHANAN SOSIO-BUDAYA REMAJA MELALUI MODEL MONOLINGUISTIK PRANCIS DALAM PEMBELAJARAN BAHASA ASING DI SMA NEGERI 4 PURWOKERTO - Tri Asiati; Monika Herliana; Rizki Utami (Dinamika Journal : Pengabdian Masyarakat, 2019)
This program generally aims to apply the result of research while the specific objectives are : (1) directing the attitudes and behaviour of teenagers in accordance  with values of local wisdom, (2) instilling a sense of love for national language and culture, (3) instilling a sense of love for regional languages and cultures, (4) inculcating the respect and the tolerance for other languages and other cultures, (5) instilling the universality and the unity of national languages, and (6) fostering the language creativity as a form of teenagers socio-cultural resilience where located at SMA Negeri 4 Purwokerto as a form of applying research results with the title "Adaptasi Model Monolinguistik Prancis dan Eksistensi Lembaga Budaya dalam Meningkatkan Ketahanan Lingua Franka” In this case, the methods used are: presentation, discussion, and practice. Finally, the indicators of success are measured through evaluations with pre-test and post-test in order to determine the effectiveness of the French monolinguistic.